Pemanfaatan Teknologi Informasi Dalam Pelatihan Pembuatan Data Pelayanan Persalinan Menggunakan Visual Studio - Aliyah, Siti; Dari, Wulan; Maisaroh, Enni (Publikasi Pengabdian Masyarakat, 2022)
Pratama Bertha Clinic Medan is one of the public health institutions whose activities are to serve the health of patients both outpatient and inpatient, there are maternity polyclinic facilities and patient inpatient rooms. The service system in the clinic has not been fully implemented optimally, resulting in the service system in the clinic being less effective and efficient. The author makes data services using visual studio as a solution to some of the problems faced. In making this application the author uses Visual Studio 2010 as a programming language and the database uses SQL Server 2008.